Loan Review, Provisioning, and Macroeconomic Linkages. (IMF Working Papers; Working Paper, 2000)
Loan review is a process routinely used by banks to assess the current value of loan portfolios. Provisioning is a technique to translate loan review results into the balance sheet. It allows for ongoing valuation of loans. Both are core elements of credit risk management and important to prudential oversight. As illustrated in this paper, valuation feeds into indicators of overall bank soundness and key macroprudential indicators. Country practices and recent moves to more forward-looking models are surveyed. Macroeconomic linkages are highlighted, including tax treatment of provisions, variables of the monetary survey, and procyclical aspects of loan valuation systems.